The First Year Developmental Crisis: Origin of Cultural Action - Solovieva, Yulia; Quintanar, Luis (Frontiers in Psychology, 2021)
According to conception of cultural historical psychology, introduced by L.S. Vigotsky, early the first year of child’s life represents specific period of development or the first psychological age. Psychological development should be differentiated from biological development and have proper objective indicators. Psychological development starts with possibility of initial cultural communication between an adult and child, within unique kind of social situation of development. The goal of the article is to describe the content of the crisis of first year of life as psychological phenomenon and to propose psychological and neuropsychological indicators for qualitative assessment of progress of psychological development at the end of the first year of life. The article opens the discussion about guiding activity of the first age, new psychological formations of the crisis of the first year and qualitative changes in social situation of development. The content of the first psychological age and crisis is presented in the article, according to proposals of cultural historical psychology. Future interdisciplinary research should be continued in order to establish optimal strategies for adult and child interaction during stable period of development and the crisis of the first year.